ANALISIS AKTIVITAS ANTIOKSIDAN JUS MANGGA SEGAR MEREK A DAN OLAHAN SENDIRI - Kusuma, Christine; Caroline, Catherine; Sukarti, Emi (Jurnal Farmasi Indonesia, 2019)
Sugary juice drinks are a practical drink culture of urban society. Various and popularbrands selling fruit juices, especially mango juice on the market. However, the large amount of fruitprocessing carried out by mango fruit juice entrepreneurs makes the prices offered on the marketquite high with a lack of information on their products. On the other hand, the number of degenerativediseases in Indonesia is also increasing. This can be overcome by consuming antioxidants in fruitjuice. In this study an antioxidant activity of brand A mango juice was compared with mango andprocessed mango juice to provide information that mango juice made by itself has higher antioxidantand economical so that it can be used to maintain health and can be used as source of antioxidants.The test method that will be used to determine antioxidant activity using the DPPH method. The resultof selected DPPH wavelength is 517 nm. The average IC50 vitamin C, mango, processed mango juice,and brand A mango juice samples were 13.95 ?g / ml, 27475.18 ?g / ml, 67589.40 ?g / ml, 143819.93?g / ml. This shows that the sample of brand A mango juice has a smaller antioxidant activity valuecompared to the processed mango juice and the mangoes without any additions.